Warning behaviors and leaked intent: Potential new avenues to prevent mass shootings. Issue 1 (24th November 2021) - Freitas, Corina; Annas, George David
Abstract: On March 12, 2018, John Laubscher, owner of AJ's Archery in Nelson, NY, had a gut feeling and refused to sell a rifle to a Syracuse University student—disrupting a mass shooting (https://www.syracuse.com/crime/2018/04/how_gun_shop_owner_thwarted_on_the_edge_su_student_from_buying_high‐capacity_rif.html . Accessed 10 Nov 2021). Prompted by this, we surveyed the opinions, beliefs, attitudes, and current practices of gun sellers in Onondaga County, NY, in regard to safe gun sales. The primary outcome was to determine which types of "concerning behaviors" are more likely to cause a seller to intervene in some manner. Secondary outcomes included the following: ascertaining the frequency of denials of customer purchases, frequency of reporting to law enforcement, and identifying any gaps that make it difficult for gun sellers to report behaviors to the authorities. Follow‐up interviews were conducted with those who were willing to speak with the authors in more depth. A response rate of 12.9% was achieved. Sixty‐two percent (62.5%) of respondents had some experience in uniformed services, with specialized training in mental or emotional crises, as well as deception detection. The majority found the training helpful in their gun selling career. Reasons for personal denials were reported as: "interest in illegal fittings, " "information revealed during conversation, " and "lack of basic knowledge of using the firearm looking to purchase." Two respondents stated that due to a lack of a "reporting protocol, " they would not report any concerns to law enforcement. The study helps inform future research in regard to surveying more sellers across NY state and nationwide.